Safety improvements by eliminating hazardous combinations - Hadad, Yossi; Laslo, Zohar; Ben-Yair, Avner (Technological and Economic Development of Economy, 2007)
In this paper we suggest the hazardous combinations method to facilitate safety improvements in technical and technological systems by eliminating combinations of major risk factors. The method is capable to significantly improve the safety level in systems as compared to a common situation when only the root causes of accidents were analysed (usually with unsatisfactory results), or where the usual procedures proved to be ineffective due to organisational, technological or financial constraints. In many cases the management decides to implement costly safety measures which have eventually only a minor effect, if at all, on preventing severe accidents. By focusing on prevention of not all recognised primary risk factors but only their hazardous combinations, both human lives and significant financial resources may be saved. Saugos gerinimas šalinant pavojingųjų veiksnių derinius Santrauka. Straipsnyje siūlomas pavojingųjų derinių metodas, kuris padeda pagerinti techninių ir technologinių sistemų saugą, šalinant didžiausios rizikos veiksnių derinius. Jis gali būti taikomas, kai visuotinai paplitusi priežasčių analizė neduoda teigiamų rezultatų arba kai įprastines procedūros nėra efektyvios dėl organizacinių, technologinių arba finansinių apribojimų. Daugeliu atvejų diegiamos brangios saugos priemones, kurios duoda nedideli efekta, galbūt užkardo stambias avarijas. Sutelkiant demesi ne i visus imanomus rizikos veiksnius, bet tik į jų pavojinguosius derinius, gali būti išgelbėtos ir žmonių gyvybės, ir sutaupyta lėšų. Reikšminiai žodžiai: saugos gerinimas, rizikos veiksniai, avarijos, priežastys, pavojingieji deriniai. First Published Online: 21 Oct 2010